Analisis Kondisi Fisik Atlet Putri Futsal SMK Muhammadiyah 1 Gresik - Ihda Amaliya; Pudjijuniarto (Jurusan Pendidikan Kesehatan dan Rekreasi, 2022)
Futsal is a sport of the big ball game. The game of futsal is not only for men who can play the game, nowadays there are also many women. This study aims to determine the level of physical condition of female futsal athletes at SMK Muhammadiyah 1 Gresik which includes speed, agility, endurance and strength. The population in this study were 15 female futsal athletes at SMK Muhammadiyah 1 Gresik. This research method uses quantitative methods with descriptive methods. The data collection technique is by using a questionnaire. The results of this study are (1) The athlete's average speed is 4.285 seconds which is categorized as Very Good. The percentage is 60% categorized as Very Good;. (2) The average endurance of athletes is 23.94 ml/kg/min which is categorized as low. The percentage of 100% in the Low category; (3) the average strength of athletes is 24.16 times which is categorized as Medium. The percentage of 93.33% is categorized as Medium; (4) The average agility of athletes is 21.34 seconds categorized as Medium. The percentage of 66.67% is categorized as Medium. So from the results of this study it can be concluded that the female athlete Futsal at SMK Muhammadiyah 1 Gresik has a moderate physical condition. Because the average physical condition of female Futsal athletes at SMK Muhammadiyah 1 Gresik is in the Medium category. Keywords: futsal; female futsal athlete, physical condition